Pendidikan Sebagai Sistem: Sinergi Tri Pusat Pendidikan dalam Mewujudkan Mutu Pendidikan Nasional - Silmi Afifah; Abdul Khobir; Sabila Faiza Al Izzati Amin; Iqlil Khoerul Ma’mun (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Education as a system demands integration between family, school, and society as formulated in the concept of the Three Centers of Education by Ki Hajar Dewantara. However, the synergy between these three centers of education has not been optimal, resulting in the low quality of national education, as indicated by the fulfillment of the National Education Standards (SNP) and various learning quality indicators. This article aims to analyze education as a system through a study of the role and relationship of the Three Centers of Education in supporting the improvement of national education quality. The study uses a library research approach through a review of academic literature and policy documents that are analyzed descriptively and analytically. The results of the study indicate that the Three Centers of Education are subsystems that are theoretically interrelated and have a strategic role in the development of student competencies. However, structural gaps were found in the form of fragmented roles, weak coordination, and the absence of a standard operational model, which has prevented synergy from being realized systematically. This article emphasizes the need to develop an integrated collaboration model as a conceptual framework to strengthen the national education system and improve education quality sustainably.